Application of the flipped classroom model based on Bloom’s Taxonomy of Educational Objectives in endodontics education for undergraduate dental students - Yaru Wei; Zhengjun Peng (PeerJ)
Introduction The current study was conducted to compare the effects of the lecture method of teaching and the flipped classroom model based on Bloom’s Taxonomy of Educational Objectives on the teaching of endodontics curriculum to undergraduate students majoring in stomatology, and to develop a standardized teaching process based on the flipped classroom model. Materials and Methods A standardized flipped classroom model based on Bloom’s Taxonomy of Educational Objectives was established. Two groups of undergraduate students majoring in stomatology received instruction in a portion of the endodontics curriculum using either the lecture method or flipped classroom model of teaching. A teaching questionnaire was administered to evaluate the students’ mastery of theoretical knowledge, understanding of learning objectives, satisfaction of teaching method, and learning interest. The SPSS 26.0 software was used for statistical analysis, and the t-test was used to compare the differences between the two groups. Results Both learning model cohorts filled out assessment questionnaires upon completion of the pilot curriculum. Compared with the responses from students in the lecture-based group, the self-rating of theoretical knowledge reported by students in the flipped classroom cohort increased by 10.9%, from 7.1 ± 0.8 to 7.9 ± 0.7 (t = 2.912, p < 0.006). Students’ test scores in the flipped classroom group increased by 17.1%, from 7.0 ± 0.8 to 8.2 ± 0.7 (t = 4.284, p < 0.001). Students’ understanding of ideological and humanistic objectives as well as medical ethics were both significantly improved by 11.4% (t = 2.267, p = 0.009) and 13.9% (t = 2.600, p = 0.014), respectively. Students’ satisfaction with the teaching model and class duration increased significantly, by 11.1% (t = 2.782, p = 0.009) and 14.3% (t = 2.449, p < 0.020), respectively. Students’ learning interest increased by 17.1% (t = 3.101, p = 0.004). The length of study time prior to class under the flipped classroom model was longer than when using the traditional lecture method (t = 3.165, p = 0.003), but the flipped classroom model shortened review time after class (t = 4.038, p = 0.001). Students’ self-reported understanding of teaching objectives improved by 8.3% (t = 1.762, p = 0.083), and satisfaction with the preview method and curriculum increased by 8.1% (t = 1.804, p = 0.081) and 11.1% (t = 1.861, p = 0.072), respectively. There was no statistically significant difference between the two groups. Conclusions The flipped classroom teaching model based on Bloom’s Taxonomy of Educational Objectives, combined with humanistic teaching objectives, can improve the efficacy of instruction, and merits popularizing and applying in the teaching of undergraduate students majoring in stomatology.